Back Cover: On the Control of Magnetic Anisotropy through an External Electric Field (Chem. Eur. J. 43/2014). Issue 43 (10th October 2014) - Goswami, Tamal; Misra, Anirban
Abstract : The tuning of spin–orbit coupling with external electric field and concomitant change in the magnetic anisotropy of a single‐molecule magnet was observed. It has been shown by DFT calculations that the application of electric field can alter the magnetic anisotropy from "easy‐plane" ( D >0) to "easy‐axis" ( D <0) type. This phenomenon is also found to bring about "Spin–Hall" type of spin separation in single molecule. For more information, see the Full Paper by T. Goswami and A. Misra on page 13951 ff.